PROBLEMS IN USING LANGUAGE LABORATORY IN ENGLISH LISTENING INSTRUCTION - Feby Akhdiyati (University of Kuningan, 2018)
This study is aimed at describing problems faced by both teachers and students in learning listening using language laboratory in SMA Sandikta, Bekasi and providing solutions to overcome those problems. The participants of the study are the eleventh-grade students of SMA Sandikta. The results of the analysis showed that there are some problems faced by the teacher and the students. The problems faced by the teacher include (1) the problems related to the teacher’s proficiency like being unable to identify the error of machine, (2) insufficient collection of master tapes which makes problem for the teacher to accommodate the material, (3) too long material make the students bored, the teacher has difficulties to select of material, and (4) the attitude of the teacher and students toward language lab. On the other hand, the problems faced by the students are (1) students’ lack of vocabulary, (2) physical aspects of students like boredom, and (3) the teacher did not give the tapescript, the students just memorize the dialog. For that reason, it was suggested to all parties to improve the knowledge in optimalizing the language laboratory.Keyword: ability; language laboratory; listening; action research.